Peran Badan Kerjasama Antar Desa Dalam Perlindungan, Pengelolaan, dan Pelestarian Hasil Pelaksanaan Program Nasional Pemberdayaan Masyarakat Mandiri Kabupaten Banyuasin - Mietha Nella (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The purpose of this study was to determine protection, management, and preservation as efforts made to provide legal guarantees, maintain sustainability, and expand the results of participatory development carried out by the PNPM MP Village Independent Community Empowerment National Program (PNPM MP) in the form of SPP (Savings and Loans). Specifically for women and the distribution of facilities The problem faced by the Inter-Village Cooperation Agency (BKAD) is the ongoing arrears from the SPP group in Banyuasin. This research takes issue by investigating the role of BKAD in protecting, managing, and preserving the results of PNPM implementation in Banyuasin District. Qualitative methods selected to research the problem being investigated. Research data was collected by in-depth interviews, observation, and documentation. Determination of informants was carried out by purposive sampling. Information validation through consistent participation, observation, member checking, and triangulation. Data were analyzed qualitatively, consisting of data collection, data reduction, data presentation, and data verification. The results of the study cover three issues. First, BKAD conducts safeguards aimed at inventorying SPP assets and properties through discussions. Second, BKAD conducts management programs by restructuring client loans, in collaboration with all teams involved in PNPM. Third, the conservation efforts carried out by BKAD have resulted in a sustainable SPP.